The participation of nurses in relation to patients in brain death - dos Santos, Rafael de Carvalho; Leite Junior, Hélio Pereira; de Souza, Keli Ferreira (Seven Editora, 2023)
The present work seeks to analyze the importance of the nurse in the performance of professional practice related to the patient diagnosed with brain death, observing the maintenance of care and the consent of family members. This study aims to provide and make the reader aware of the knowledge of the diagnosis of brain death along with the importance of the attribution of the nursing team in the face of the patient in brain death and in the care of their family members at the time of loss, aiming at the importance of organ donation.DOI:https://doi.org/10.56238/alookdevelopv1-104